2021
DOI: 10.1186/s12866-021-02305-z
|View full text |Cite
|
Sign up to set email alerts
|

Infants with cystic fibrosis have altered fecal functional capacities with potential clinical and metabolic consequences

Abstract: Background Infants with cystic fibrosis (CF) suffer from gastrointestinal (GI) complications, including pancreatic insufficiency and intestinal inflammation, which have been associated with impaired nutrition and growth. Recent evidence identified altered fecal microbiota taxonomic compositions in infants with CF relative to healthy infants that were characterized by differences in the abundances of taxa associated with GI health and nutrition. Furthermore, these taxonomic differences were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…One key features of the CF gut microbiome is decreased species diversity [ 7 , 12 , 52 , 53 , 54 ] ( Figure 1 ). In addition, paediatric studies have demonstrated that the CF gut microbiome diversifies and matures at a significantly slower rate than that of a healthy child [ 54 , 55 , 56 ]. Compositionally, the CF gut microbiome also differs from that of the healthy gut.…”
Section: The Cf Gut Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…One key features of the CF gut microbiome is decreased species diversity [ 7 , 12 , 52 , 53 , 54 ] ( Figure 1 ). In addition, paediatric studies have demonstrated that the CF gut microbiome diversifies and matures at a significantly slower rate than that of a healthy child [ 54 , 55 , 56 ]. Compositionally, the CF gut microbiome also differs from that of the healthy gut.…”
Section: The Cf Gut Microbiomementioning
confidence: 99%
“…Recent advancements in metagenomic methods have enhanced the ability to characterise the functionality of the gut microbiota, thereby elucidating the physiological consequences of dysbiosis. It has been demonstrated that the CF gut microbiome displays an increased capacity to metabolise nutrients, antioxidants, and short-chain fatty acids (SCFAs), as well as a relatively decreased propensity to synthesise fatty acids [ 7 , 56 , 59 ].…”
Section: The Cf Gut Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Infants and young children with CF are dramatically affected and typically require intensive medical attention from birth, with nutritional and growth deficits due to pancreatic insufficiency and progressive lung disease 20,21 . Dramatic alteration of gut microbiota composition is a hallmark of both infants and adults with CF, correlating with linear growth inhibition and increased fecal fat content and markers of intestinal inflammation [22][23][24][25][26][27][28] . Notable compositional differences in the microbiota found across studies between control and CF individuals from both infant and adult cohorts include increased Proteobacteria and diminished levels of Bacteroidetes which manifest following birth and do not resolve 22,23,26,27,29 .…”
mentioning
confidence: 99%
“…Studies showed that the intestinal microbiota of pwCF differs from that of their healthy peers. Furthermore, researchers concluded that the intestinal microbiome of the patients affected by CF diversifies and matures with more difficulty compared to the healthy children [ 66 , 74 ]. Nielsen et al concluded in their study that a CF child, even at fifteen years old, does not achieve the same microbiome richness as a healthy one-year-old child [ 75 ].…”
Section: Impact Of Altered Gut Microbiota In Cystic Fibrosismentioning
confidence: 99%